The Regionalist Vision of Henry Wright: Lessons in Sustainability - Larsen, Kristin (International Planning History Society Proceedings, 2016)
Though lesser known than his Regional Planning Association of America colleagues – Clarence Stein, Lewis Mumford, and Benton MacKaye – Henry Wright played a key role in implementing and promoting critical regional planning ideals. In doing so, he embraced what Wheeler (2002) characterizes as “ecological regionalism” and more recently Berke (2008) describes as the “environmentally sustainable urban form” (p. 395). After earning his degree in architecture at the University of Pennsylvania, Wright spent his early professional years in the office of nationally prominent landscape architect George Kessler. Here he gained a sensitivity to site design, including grading and infrastructure development, and a broadening understanding of natural systems and networks. His subsequent employment with the Emergency Fleet Corporation designing communities for war workers during World War I, established his expertise in economically designing communities. During the 1920s and until his death in 1936, he applied this expertise to design communities that reflect many of the current criteria of sustainability, new regionalism, and green infrastructure. This paper examines archival writings of Wright, his contemporaries, and more recent explorations of sustainability, green infrastructure, and new regionalism to assess the elements of Wright’s community planning, site design, and broader regionalist ideas that prefigured these modern concepts. As Planning Advisor to the New York Commission of Housing and Regional Planning, his contributions towards a 1926 proposal for statewide planning forms a critical component of this examination. Further, his lesser known articles on town planning, land development, and the economics of housing design offer a sustained perspective regarding the dynamics of his contributions to regionalism. These include conceptual new town designs integrating intensive mixed use urban areas punctuated with outlying parks as part of a balanced regional network of communities. A comparative and critical analysis of these contributions within the context of the contributions of his RPAA colleagues and regional scholarship today highlights his legacy as an architect, landscape architect, and planner.